A H+-triggered bubble-generating nanosystem for killing cancer cells. Issue 72 (4th August 2016) - Yang, Lili; Wen, Zuhuang; Long, Yijuan; Huang, Ning; Cheng, Yuan; Zhao, Li; Zheng, Huzhi
Abstract : A bubble-generating nanosystem can kill cancer cells by the quick release of CO2 bubbles. Abstract : We constructed a H + -triggered bubble-generating nanosystem (BGNS), which generated CO2 bubbles in the acidic environment of lysosomes after being internalized by cancer cells. The quickly generated bubbles caused enhanced lysosomal membrane permeabilization. As expected, H + -triggered BGNS possessed remarkable cytotoxicity against MCF-7 breast cancer cells, and successfully overcame the multidrug resistance of MCF-7/ADR cells.